The unconscious sibling rivalry in psychoanalytic institutions - Simona Reghintovschi (Frontiers in Psychology)
What unconscious elements fuel the ‘radioactive atmosphere’ of psychoanalytic institutions – those unconscious sources of the chronic conflicts that sometimes plague the relationships among members of psychoanalytical societies and obscure the path of a constructive resolution of conflicts, creating a toxic climate that stultifies members’ creativity, hindering progress and further development? An empirical research was conducted using the psychoanalytically informed research interview as an experimental situation. The main findings indicates unconscious sibling rivalry as the source of conflict in the psychoanalytic institution studied, along with narcissism of minor differences. The implications for psychoanalytic training are discussed.